2012
DOI: 10.1093/carcin/bgs112
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease, Porphyromonas gingivalis serum antibody levels and orodigestive cancer mortality

Abstract: Periodontitis, the progressive loss of the alveolar bone around the teeth and the major cause of tooth loss in adults, is due to oral microorganisms, including Porphyromonas gingivalis. Periodontitis is associated with a local overly aggressive immune response and a spectrum of systemic effects, but the role of this condition in orodigestive cancers is unclear. We prospectively examined clinically ascertained periodontitis (N = 12,605) and serum IgG immune response to P.gingivalis (N = 7852) in relation to oro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
319
4
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(345 citation statements)
references
References 31 publications
18
319
4
4
Order By: Relevance
“…A recent study (Ahn et al 2012) followed up participants in NHANES III and reported that periodontitis was associated with increased orodigestive cancer mortality (OR = 2.28, 95%CI 1.17-4.45). There was a trend for an increase in risk with increasing severity of periodontitis.…”
Section: Commentmentioning
confidence: 99%
“…A recent study (Ahn et al 2012) followed up participants in NHANES III and reported that periodontitis was associated with increased orodigestive cancer mortality (OR = 2.28, 95%CI 1.17-4.45). There was a trend for an increase in risk with increasing severity of periodontitis.…”
Section: Commentmentioning
confidence: 99%
“…Among those, periodontal diseases are complex polymicrobial inflammatory diseases associated with dysbiosis of the dental biofilm that induces a long-lasting chronic inflammation of the periodontal supporting tissues, leading to alveolar bone destruction, and eventual tooth loss [6]. Over the years, strong evidence has accumulated to indicate that the pathogenic microbiota and the chronic inflammation established in periodontitis contribute to the onset and/or progression of several systemic inflammatory diseases such as cardiovascular diseases [7,8], diabetes [9], obesity [10], metabolic syndrome [11], respiratory disease [12], cancer [13], chronic kidney disease (CKD) [14] and rheumatoid arthritis (RA) [15]. Most research on the periodontitis-systemic disease relationship, however, has not determined causality, and the link between these diseases are bi-directional associations [16].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear and oxidative DNA damage area increased in subjects with periodontal disease, and genetic damage is a critical event not only in the initiation phase but also in the promotion and progression phases, which could be related to carcinogenesis events. Moreover, recent studies have associated periodontitis with some cancer including head and neck cancer [44], pancreatic cancer [45], colon cancer [46], and orodigestive cancers [47], which are relevant to the control of this disease and to promote the importance of good oral health.…”
Section: Resultsmentioning
confidence: 99%